2022
DOI: 10.3390/ijms232314972
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Maternal Plasma Aberrant miRNA Expression Associated with Spontaneous Preterm Birth

Abstract: Spontaneous Preterm Delivery (sPTD) is one of the leading causes of perinatal mortality and morbidity worldwide. The present case–control study aims to detect miRNAs differentially expressed in the first trimester maternal plasma with the view to identify predictive biomarkers for sPTD, between 320/7 and 366/7 weeks, that will allow for timely interventions for this serious pregnancy complication. Small RNA sequencing (small RNA-seq) of five samples from women with a subsequent sPTD and their matched controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Mavreli et al conducted a case-control study to identify differentially expressed miRNAs in first-trimester maternal plasma, aiming to predict spontaneous preterm delivery (sPTD). Specific miRNAs like miR-23b-5p and miR-125a-3p were identified as potential early predictors for sPTD, offering a foundation for non-invasive predictive tests and timely interventions [33].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mavreli et al conducted a case-control study to identify differentially expressed miRNAs in first-trimester maternal plasma, aiming to predict spontaneous preterm delivery (sPTD). Specific miRNAs like miR-23b-5p and miR-125a-3p were identified as potential early predictors for sPTD, offering a foundation for non-invasive predictive tests and timely interventions [33].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a significant number of miRNAs have been reported to be significantly downregulated in preterm labor, such as hsa-miR-23b-5p and hsa-miR-125a-3p [33]. This indicates that the reduction in certain miRNAs may also contribute to the initiation of preterm labor.…”
Section: Positive Correlationmentioning
confidence: 99%
“…38 Many miRNAs are aberrantly expressed in PTB pregnancies, including miR-18a-3p, miR-222-3p, miR-494-3p, miR-98-3p, miR-224-5p, miR-760, miR-143, miR-30e-3p, miR-199b, and miR-125a-3p. [39][40][41][42] Pavlek et al reported that miR-29b was associated with perinatal inflammation in preterm infants. 43 In addition, Peng and co-workers revealed that miR-199a-3p suppressed cervical epithelial cell inflammation by inhibiting the HMGB1/TLR4/NF-κB pathway in PTB.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs exert a critical effect on gene expression as well as various physiological and pathological processes, due to their posttranscriptional regulation through binding to the 3′UTR of target genes 38 . Many miRNAs are aberrantly expressed in PTB pregnancies, including miR‐18a‐3p, miR‐222‐3p, miR‐494‐3p, miR‐98‐3p, miR‐224‐5p, miR‐760, miR‐143, miR‐30e‐3p, miR‐199b, and miR‐125a‐3p 39–42 . Pavlek et al reported that miR‐29b was associated with perinatal inflammation in preterm infants 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Mavreli et al [ 13 ] introduced miR-125a-3p as a promising early biomarker for prediction of spontaneous preterm birth. Mir-125a-3p was identified as a potential biomarker for the early prediction of spontaneous preterm birth using small RNA-seq and confirmed by qRT-PCR.…”
mentioning
confidence: 99%